Disclosure of sustainability report and accounting conservatism - Putri, Magdalena Lisanti; Andreas, Hans Hananto; Chang, Ming Lei (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2023)
Disclosure of sustainability reports is a form of corporate social and environmental responsibility. The company's quality and initiatives in disclosing sustainability reports will impact the preparation of financial reports under the concept of accounting conservatism. This study aims to provide empirical evidence of the effect of sustainability report disclosure on applying accounting conservatism principles. This study comprises manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) in 2017–2020. The number of samples used in this study was 74, based on the purposive sampling method. The data analysis method in this research is a quantitative analysis using panel data regression analysis with the Random Effect Model (REM). The results of this study indicate that disclosure of sustainability reports has a positive effect on accounting conservatism. This research's contribution is to help companies decide what their corporate responsibility efforts should prioritize. The companies should be more aware of the effects of accounting conservatism and different sustainability report disclosures.